Harvest types and times of gliphosate application in the eradication of sugarcane ratoons - Silva, Marcelo de Almeida; Carlin, Samira Domingues; Caputo, Marina Maitto (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate sensibility of four sugarcane genotypes to gliphosate application for the eradication of ratoons of two ages, and in two crop systems, in a Rhodic Eutrudox. The product was applied in the dose (a.i.) of 2,400 g ha-1 to the 40 and 55 day-old shoots of the third cut harvest. In order to quantify the action of the glyphosate, alive and dead tillerings were counted in the 30th, 45th and 60th day after its application. In relation to the percentage of tillerings death, there were differences among the genotypes as for the susceptibility to the glyphosate. The applied dose was not enough to eradicate 100% of the tillerings, but for the genotypes IAC87-3184, RB835486 and SP87-344 the control was superior to 80%, being considered sensitive/intermediate, while the IAC91-5155 was considered tolerant. Crop system did not interfere in the glyphosate efficiency for ratoon elimination, however, the application made to 40 day-old shoots presented the largest died tillerings percentage.